ANALISIS POLA SEBARAN UNSUR-UNSUR LOGAM BERAT MENGGUNAKAN METODE KELISTRIKAN BATUAN DI DAERAH PERTAMBANGAN EMAS KABUPATEN BANDUNG - Rhistanto Faturohman Suhanto; Mokhamad Rizki Ramdhani; Achmad Wahyu Pratama; Eleonora Agustine (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Exploration of gold mining in Pangalengan, Bandung is one of traditional and illegal method used by villager there. The exploration gives a lot of environmental damage such as landscape and structure changing, also pollution of nature because there is no control of sewerage system or tailing gold system for the likes of Mercury (Hg) and Lead / Plumbum (Pb). The objective of this research is to know the trend pattern of mining waste distribution in Pangalengan, Bandung using Electricity Method with measurement parameter of conductivity (EC), Total Dissolved Solid (TDS), and acidity level (pH). There were two methods to take the measurement, first, took the soil sample by using coring with 0.3 meters deep with 2 inch diameter at the riverbank and channel from the sewerage places which has heavy metal elements. And second is laboratory test. The increase in heavy metal trend pattern usually has an increase in mining areas, and decrease departs from mining area. Heavy metal hoarding usually take an increase in the area of upper course of the river, it happens allegedly because of he of water flow rate. Keywords: Gold Mine, Heavy Metal, EC, TDS, Environmental Geophysics, Pollutant, Heavy Metal, Hg, Pb.